IMMUNOREGULATION OF MULTIPLE SCLEROSIS BY HELMINTH THERAPY - Editha Renesteen (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2020)
Multiple sclerosis (MS) is a chronic inflammatory disease of the central nervous system (CNS) which is characterized by the recruitment of T cells into the CNS, leading to demyelination and axonal damage. Currently, there are limited options for MS therapy, thus researchers start to use helminths therapy as a new therapeutic agent. Helminths are promising organisms to treat autoimmune diseases like MS by interfering the host’s immune responses. Several helminths, including Trichinella spiralis, Trichuis suis, Fasciola hepatica, Schistosoma japonicum and Schistosoma mansoni are under investigation in animal models for MS, experimental autoimmune encephalitis (EAE). Furthermore, Trichuis suis, Fasciola hepatica and Schistosoma mansoni are being examined in patients. This review outlines basic insight of MS, immunoregulation mechanisms induced by helminths, current helminths therapy for MS as well as helminths therapy for MS application in the future.